Penimbunan Barang Perspektif Filsafat Hukum Islam - Musyahid, Achmad; Alamsyah, Alamsyah; Madjid, Sitti Saleha; Rufaida, Erty Rospyana (Universitas Muhammadiyah Makassar, 2023)
The Al-Qur'an provides freedom in trade which is marked by the concept of buying and selling. However, this buying and selling is sometimes tainted by the behaviors of individuals or groups who hoard goods which cause instability in the economy which results in crises and even inflation. This is none other than to get a big advantage. The seller of the goods deliberately keeps the goods and will sell them when the price of the goods rises. Therefore, in carrying out trading business activities or in all other forms of seeking sustenance, it must be carried out with a fair concept, not in a way that harms only one party or benefits only one party, but must be based on the way that Allah swt. pleased. This study aims to find out the basic concept of hoarding of goods (Ihtikâr), to know the concept of hoarding of goods from the perspective of Islamic legal philosophy, and to be able to find out the things that are a factor in the occurrence of hoarding of goods (Ihtikâr). The methodology used by researchers is descriptive qualitative method. With an approach to the philosophy of Islamic law. The results of the study show that hoarding of goods is basically prohibited or unlawful. Whereas in the perspective of Islamic legal philosophy with the concept of Mahasin al-ahkam or mazaya al-ahkam (the virtues of Islamic law) and Thawabi al-ahkam (characteristics of Islamic law) arising from the hoarding process, the law changes to be permissible with considerations for the benefit of the ummah, one one of them is the stockpiling of basic commodities carried out by Bulog by preparing food reserves when a staple food crisis occurs and maintaining market price stability.